2010
DOI: 10.1161/circulationaha.109.897330
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte Modulation of High-Density Lipoprotein Cholesterol

Abstract: Background-Adipose harbors a large depot of free cholesterol. However, a role for adipose in cholesterol lipidation of high-density lipoprotein (HDL) in vivo is not established. We present the first evidence that adipocytes support transfer of cholesterol to HDL in vivo as well as in vitro and implicate ATP-binding cassette subfamily A member 1 (ABCA1) and scavenger receptor class B type I (SR-BI), but not ATP-binding cassette subfamily G member 1 (ABCG1), cholesterol transporters in this process. Methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(140 citation statements)
references
References 55 publications
4
133
2
1
Order By: Relevance
“…Although these processes may infl uence HDL-C levels, our data and the experimental evidence for an ADN effect on apoA-I and ATP-binding cassette transporter expression ( 4,22,23 ) support a direct, triglyceride-independent effect of ADN on HDL-C. Recently, it has been reported that the upstream effects of ADN are mediated by activation of ceramidase and its effects on the formation of sphingosine-1-phosphate (S1P) ( 29 ).…”
Section: Mediational Effect Of Total Adn and Its Fractions On Hdl-c Cmentioning
confidence: 49%
See 1 more Smart Citation
“…Although these processes may infl uence HDL-C levels, our data and the experimental evidence for an ADN effect on apoA-I and ATP-binding cassette transporter expression ( 4,22,23 ) support a direct, triglyceride-independent effect of ADN on HDL-C. Recently, it has been reported that the upstream effects of ADN are mediated by activation of ceramidase and its effects on the formation of sphingosine-1-phosphate (S1P) ( 29 ).…”
Section: Mediational Effect Of Total Adn and Its Fractions On Hdl-c Cmentioning
confidence: 49%
“…In these animals, there are decreases in apoA-I levels and in the expression of ATP-binding cassette transporters in liver, suggesting that ADN defi ciency may impair HDL assembly. Recent reports have also identifi ed the presence of ATP-binding cassette transporters in adipocytes and have confi rmed an active role for adipose tissue in the synthesis of HDL ( 4,23 ). However, differences in HDL metabolism between rodents and humans ( 24 ) and in the posttranslational modifi cations of ADN, which have functional implications and vary by species ( 25 ), preclude the extrapolation of ADN and HDL-C mouse fi ndings to humans.…”
Section: Mediational Effect Of Total Adn and Its Fractions On Hdl-c Cmentioning
confidence: 99%
“…SR-BI is required for HDL modulation of endothelial cell phenotype ( 56,60,64 ) and for the actions of HDL in EPC ( 57 ). SR-BI also mediates the actions of apoA-I and/or HDL in neutrophils ( 25 ), adipocytes ( 111 ), and pancreatic ␤ cells ( 36 ).…”
Section: Sr-bimentioning
confidence: 99%
“…Heavy uptake of glucose from the peritoneal dialy sis fluid can also lead to a rise in plasma triglyceride levels 3 . Other factors that modify the serum lipid profile in this population include systemic inflammation, malnutrition, use of lipid-altering drugs (such as statins and fibrates), and exposure to sevelamer -a phosphate binding resin that markedly lowers serum cholesterol levels by binding and sequestering bile acids in the intestinal tract 7,8 . Furthermore, use of steroids and certain immunosuppressive medications, such as rapamycin and calcineurin inhibitors, that are frequently administered to renal transplant recipients can also affect lipid metabolism and serum lipid profile 3 .…”
mentioning
confidence: 99%